Contraceptive practices amongst HIV-positive women on antiretroviral therapy attending an ART clinic in South Africa - Ezekiel E. Oni; Andrew Ross; Stephan van der Linde (AOSIS, 2013)
Background: Effective contraceptive practices amongst HIV-positive women of reproductive age have been shown to reduce mother-to-child transmission of HIV by preventing unplanned pregnancies. However, most antiretroviral therapy (ART) programmes focus on treatment,neglecting comprehensive contraceptive services. This results in a high frequency of pregnancies amongst HIV-positive women attending the ART clinic of a regional hospital north of Durban. Objectives: This research aimed to explore contraceptive use amongst HIV-positive women attending an ART clinic by determining, (1) prevalence of contraceptive use, (2) pregnancy rate, (3) contraceptive preferences and (4) factors associated with contraceptive use. Methods: In this observational, analytical, cross-sectional study of 420 women, aged 15to 49 years, participants were selected by systematic random sampling. They completed standardised questionnaires. Results: Of all participants, 95% of the participants used contraception. Factors associated with contraceptive practice were knowledge of HIV status 292 (72.8%), health worker advice 84 (20.9%), and spousal insistence 33 (8.2%). Of the 130 women (31%) who had fallen pregnant whilst on ART, 73 (56.2%) said that the pregnancy had been unplanned, whilst 57 (43.8%) had wanted to fall pregnant because of: partner's insistence (45.6%), desire for a child (36.8%),desire to conceal HIV status (15.8%), not wanting to die childless (5.3%), and death of aprevious child (1.8%). Conclusion: Contraceptive use amongst these women was high but the number of pregnancies is a cause for concern. Information regarding contraceptive use should therefore be providedat all ART clinics.